Analisis komitmen dan kompetensi dan pengaruhnya terhadap kinerja guru - Zamhir Basem; Edi Syafri; Slamet Wahyudi (STIE Bangkinang Publishing, 2023)
Realizing high-quality graduates requires good teacher performance. Therefore, it is necessary to know what factors influence the teacher's performance. This study only pays attention to the variables of commitment and competence, which are considered capable of influencing teacher performance. Therefore, the purpose of this study was to determine and analyze the effect of commitment and competence on teacher performance. This study uses a quantitative approach. The research data uses primary and secondary data obtained using interviews, questionnaires, observations, and research files. The population in this study was all teachers at SMA Negeri 02, Kubu Babussalam District, totaling 57 people, and all of them were used as samples, so the sampling technique was carried out using the census method. The data analysis tool was performed using a linear regression model. The results of this study concluded that, simultaneously and partially, commitment and competence have a significant effect on the performance of teachers at SMA Negeri 02, Kubu Babussalam District. This result explains that the more committed the teacher, the better his work or performance, and vice versa. Likewise with the competence of the teacher, the better the competency of the teacher, the better the performance of the teacher, and vice versa.